On-chip ultrasensitive and rapid hydrogen sensing based on plasmon-induced hot electron–molecule interaction - Long Wen; Zhiwei Sun; Qilin Zheng; Xianghong Nan; Zaizhu Lou; Zhong Liu; David R. S. Cumming; Baojun Li; Qin Chen (Light: Science & Applications, 2023)
Interface dipole modulated hot-electron ejection enables an on-chip electric readout plasmonic hydrogen sensor with abnormal S-shape I–V and advanced sensing performance at a limit of detection of 1 ppm.